"Sexplorando": Sexual Practices and Condom Use among an Internet‐Based Sample of Men and Women in Puerto Rico. (17th July 2014) - Rodriguez‐Diaz, Carlos E.; Collazo, Erika; Dodge, Brian; Roman‐Rivera, Aixa; Candelaria‐Rosa, Exa; Colon‐Colon, Marcilyn; Herbenick, Debby
Abstract Introduction Despite the wealth of literature addressing sexual practices and condom use among men and women, very little data are available among Hispanic/Latino populations and in the Caribbean Region. This study adds to the existing literature on sexual practices and condom use in Puerto Rico (PR) and provides comparisons based on sex given the need for more current information on the sexual characteristics and condom use rates among understudied populations. Aim The aim of this study was to assess the rates of sexual practices and condom use among adults, aged 21–49, in PR. Methods We report the prevalence of lifetime and recent (past 3 months) sexual practices by sex, as event‐level condom use rates, and condom familiarity and accessibility in an online‐based sample of adult men and women in PR. Main Outcome Measures The main variables assessed include sociodemographic characteristics, solo and partnered sexual practices, and condom use frequencies, as well as familiarity and accessibility to male and female condoms. Results Overall, 93% of the sample reported having been sexually active (engaged in oral, vaginal, and/or anal sex) in their lifetime and 78% reported sexual practices in the past 3 months. As in other studies Hispanic/Latino populations, reported rates of anal intercourse (AI) among both men and women were relatively high. Overall, a greater proportion of men reported condom use during all sexual practices (41% vaginal intercourse (VI); 65% receptive AI; 46% insertive AI) than women (22% VI; 18% AI). Conclusions These findings provide current sexual practice and condom use frequency rates that can aid in the understanding of the particular sexual health needs of Hispanic/Latino populations as well as of other groups in the Caribbean. It also serves for the development of future studies and sexual health promotion programs, including comprehensive sexual health care. Rodriguez‐Diaz CE, Collazo E, Dodge B, Roman‐Rivera A, Candelaria‐Rosa E, Colon‐Colon M, and Herbenick D. "Sexplorando": Sexual practices and condom use among an Internet‐based sample of men and women in Puerto Rico. J Sex Med 2014;11:2385–2395.